Applying PLEASE Strategy to Teach Writing Skill on Students with Different Linguistic Intelligence - Dyah Aminatun; Ngadiso Ngadiso; Sri Marmanto (Universitas Teknokrat Indonesia, 2018)
PLEASE Strategy is a mnemonic that provides learners with a road map for writing a text. It is a strategy when a teacher teaches the students an acronym to remember each step in writing. PLEASE strategy will help students to write, to start the first sentence, and to put the data information in their writing. This article refers to an experimental study on the effectiveness of PLEASE Strategy to teach writing at the eleventh grade of SMA Negeri 1 Ngemplak. The samples were two classes, experimental class which was taught using PLEASE Strategy and control class which was taught using Guided Writing Strategy. To gain the data, two instruments were use, writing test and linguistic intelligence test. The data were, then, analyzed by using Multifactor Analysis of Variance ANOVA 2x2 and Tukey test. Before conducting the ANOVA test, pre-requisite test namely normality and homogeneity test were conducted. The findings of this research are: (1) PLEASE strategy is more effective than Guided Writing Strategy to teach writing; (2) The students having high linguistic intelligence have better writing skill than those having low linguistic intelligence; and (3) There is an interaction between teaching strategies and students’ linguistic intelligence in teaching writing.PLEASE Strategy is a mnemonic that provides learners with a road map for writing a text. It is a strategy when a teacher teaches the students an acronym to remember each step in writing. PLEASE strategy will help students to write, to start the first sentence, and to put the data information in their writing. This article refers to an experimental study on the effectiveness of PLEASE Strategy to teach writing at the eleventh grade of SMA Negeri 1 Ngemplak. The samples were two classes, experimental class which was taught using PLEASE Strategy and control class which was taught using Guided Writing Strategy. To gain the data, two instruments were use, writing test and linguistic intelligence test. The data were, then, analyzed by using Multifactor Analysis of Variance ANOVA 2x2 and Tukey test. Before conducting the ANOVA test, pre-requisite test namely normality and homogeneity test were conducted. The findings of this research are: (1) PLEASE strategy is more effective than Guided Writing Strategy to teach writing; (2) The students having high linguistic intelligence have better writing skill than those having low linguistic intelligence; and (3) There is an interaction between teaching strategies and students’ linguistic intelligence in teaching writing.